Use of the EN 12390-10 outside protected test as a tool for determining carbonation resistance. Issue 10 (10th May 2022) - Harrison, Thomas Alexander; Jones, Rod; Kandasami, Sivakumar; Newlands, Moray
Abstract : From first principles, criteria for the EN 12390-10 outside protected test have been developed and compared with existing practice. These criteria align well with the UK recommendations but are more conservative than the current French and Spanish requirements. The EN 12390-10 outside protected test is unsuitable for classification as this would require anybody using the procedure with identical concrete to get the same result. Unfortunately, current tests that are suitable for classification, whilst safe, do not reflect the real performance of slowly reacting cements. Improving the test for classification purposes will take time and meantime the use of the EN 12390-10 outside protected test and the criteria given in this paper provides a procedure by which both sustainability and durability may be achieved. The downside of this test is its slowness and, therefore, it is only suitable for type testing or the determination of limiting values and other criteria to be used in specifications or production.